New Excavations of a Section of the Late Roman (Valens) Aqueduct in İstanbul - Derya Talay; Michael Deniz Yılmaz; M. Bahattin Aydın; Veysi Gündüz (Anadolu Araştırmaları)
İstanbul, throughout history, has been home to several civilisations and has been named differently by each civilisation. As the direct and indirect source of life, the need for water was one of the most important requirements of İstanbul’s populace. In this context, the city is known to have received its first long-distance aqueduct during the Roman Empire under the reign of Emperor Hadrian (AD 117-138). Later, a second aqueduct was constructed during the reign of Emperor Valens (AD 364- 378).A vaulted channel belonging to a Roman Age aqueduct discovered under the foundations of old structures removed during an urban transformation project constitutes the subject of this work. The aqueduct composed of a vaulted channel is located within Gaziosmanpaşa Municipality’s Bağlarbaşı District near Adsız Nefer Street and holds important information regarding the aqueducts of İstanbul which began to be utilized to bring water from far destinations.With knowledge from previous research, this work aims to investigate and identify which aqueduct line the channel belongs to and to contribute to the knowledge regarding the city’s water supply.